Pengaruh Pendukung Selebriti, Citra Merek, dan Kepercayaan Merek terhadap Keputusan Pembelian Produk Somethinc - Faudji, Novayanti; Resmi, Siti; Utami, Alivia Meyrizka (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2024)
The purpose of this study was to analyze the influence of celebrity endorsers, brand image, and brand trust on purchasing decisions for Somethinc products. The data used in this study are primary data obtained through Google forms distributed via WhatsApp and Instagram. This study was processed using the IBM SPSS 26 program. Data were analyzed starting from instrument testing using validity and reliability tests, classical assumption tests, model feasibility tests (F tests), hypothesis tests (t tests), and determination tests. The results of this study indicate that the celebrity endorser variable does not affect the purchasing decision for Somethinc products, while the brand image and brand trust variables each have a positive and significant effect on the purchasing decision for Somethinc products. The results of this study are expected to be a recommendation for PT Royal Pesona Indonesia that Somethinc's brand image and brand trust have an influence on consumer purchasing decisions.